Magnitude and meaningfulness of change in SF-36 scores in four types of orthopedic surgery - Buchbinder Rachelle; Nilsdotter Anna; Osborne Richard H; Busija Lucy; Roos Ewa M (Health and Quality of Life Outcomes, 2008)
Abstract Background The Medical Outcomes General Health Survey (SF-36) is a widely used health status measure; however, limited evidence is available for its performance in orthopedic settings. The aim of this study was to examine the magnitude and meaningfulness of change and sensitivity of SF-36 subscales following orthopedic surgery. Methods Longitudinal data on outcomes of total hip replacement (THR, n = 255), total knee replacement (TKR, n = 103), arthroscopic partial meniscectomy (APM, n = 74) and anterior cruciate ligament reconstruction (ACL, n = 62) were used to estimate the effect sizes (ES, magnitude of change) and minimal detectable change (sensitivity) at the group and individual level. To provide context for interpreting the magnitude of changes in SF-36 scores, we also compared patients' scores with age and sex-matched population norms. The studies were conducted in Sweden. Follow-up was five years in THR and TKR studies, two years in ACL, and three months in APM. Results On average, large effect sizes (ES≥0.80) were found after orthopedic surgery in SF-36 subscales measuring physical aspects (physical functioning, role physical, and bodily pain). Small (0.20–0.49) to moderate (0.50–0.79) effect sizes were found in subscales measuring mental and social aspects (role emotional, vitality, social functioning, and mental health). General health scores remained relatively unchanged during the follow-up. Despite improvements, post-surgery mean scores of patients were still below the age and sex matched population norms on physical subscales. Patients' scores on mental and social subscales approached population norms following the surgery. At the individual level, scores of a large proportion of patients were affected by floor or ceiling effects on several subscales and the sensitivity to individual change was very low. Conclusion Large to moderate meaningful changes in group scores were observed in all SF-36 subscales except General Health across the intervention groups. Therefore, in orthopedic settings, the SF-36 can be used to show changes for groups in physical, mental, and social dimensions and in comparison with population norms. However, SF-36 subscales have low sensitivity to individual change and so we caution against using SF-36 to monitor the health status of individual patients undergoing orthopedic surgery.